2010
DOI: 10.1159/000311520
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Perfusion Measurement in Brain Tumours at 3 Tesla MR: Arterial Spin Labeling versus Dynamic Susceptibility Contrast-Enhanced MRI

Abstract: Purpose: To prove the feasibility of arterial spin labeling (ASL) to explore brain tumors by comparing dynamic susceptibility contrast-enhanced MRI to ASL at 3T MR. Materials and Methods: Twenty-seven patients were included presenting 9 gliomas, 10 metastases and 8 meningiomas. All were explored by a pseudo-continuous ASL and dynamic susceptibility contrast-enhanced T2* perfusion sequence. Two neuroradiologists analyzed the cerebral blood flow (CBF) maps to assess feasibility, examination quality and quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 59 publications
2
41
1
1
Order By: Relevance
“…Initial reports demonstrated that ASL and DSC show largely concordant results in terms of identifying this tumor, and distinguishing it from contrast-enhancing mimics (89)(90)(91)(92). Higher CBF in GBM correlates with genetic markers (such as epidermal growth factor receptor) and is associated with shorter progression free survival time (93).…”
Section: Primary Cns Neoplasmsmentioning
confidence: 99%
“…Initial reports demonstrated that ASL and DSC show largely concordant results in terms of identifying this tumor, and distinguishing it from contrast-enhancing mimics (89)(90)(91)(92). Higher CBF in GBM correlates with genetic markers (such as epidermal growth factor receptor) and is associated with shorter progression free survival time (93).…”
Section: Primary Cns Neoplasmsmentioning
confidence: 99%
“…For each tumor, mean absolute (aTBF) and relative tumor blood flow (rTBF) were measured in each ROI (Fig 1A). [35][36][37][38] Interrater agreement was evaluated by the To determine absolute tumor blood flow, we placed the ROI in the enhancing lesion (A, black circle). Relative TBF was obtained by normalizing the aTBF by a blood flow measurement from the reference region (white circle).…”
Section: Image Analysismentioning
confidence: 99%
“…20,27 In terms of detection of gliomas and metastases, ASL and DSC-MR imaging also showed similar diagnostic yields. 28,29 However, ASL has the advantages of better signal-to-noise ratio, fewer distortion effects secondary to hemorrhage, and the potential for quantification. 17 More definitive studies comparing the 2 modalities will be needed in the patient population with postradiation metastasis.…”
Section: Discussionmentioning
confidence: 99%